2022
DOI: 10.1007/s10984-022-09406-0
|View full text |Cite|
|
Sign up to set email alerts
|

Physical home learning environments for digitally-supported learning in academic continuing education during COVID-19 pandemic

Abstract: Since the outbreak of the COVID-19 pandemic in 2020, digital technologies for distance learning have been used in educational institutions worldwide, raising issues about social implications, technological development, and teaching and learning strategies. While disparities regarding access to technical equipment and the internet (‘the digital divide’) have been the subject of previous research, the physical learning environment of learners participating in online learning activities has hardly been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…Therefore, not every country has the means and resources to adjust to online learning. A study showed that 85% of the institutions in Europe quickly replaced in-person education with online learning, while only 29% of African institutions met online education requirements [ 6 ]. Moreover, since the beginning of February 2020, Chinese colleges and universities have used different learning modes, including online learning based on different platforms, to achieve the goal of suspending classes without suspending learning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, not every country has the means and resources to adjust to online learning. A study showed that 85% of the institutions in Europe quickly replaced in-person education with online learning, while only 29% of African institutions met online education requirements [ 6 ]. Moreover, since the beginning of February 2020, Chinese colleges and universities have used different learning modes, including online learning based on different platforms, to achieve the goal of suspending classes without suspending learning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be borne in mind that all the students had their own minimum technical resources essential for optimal use of the designed seminars. This is relevant since an implementation of online teaching must overcome the inequalities between students in access to technologies that can negatively affect the learning opportunities of disadvantaged students (Beaunoyer et al 2020); as some studies have highlighted, adequate conditions in home learning environments are very relevant to guarantee learning based on high motivation and well-being and a low level of stress during online sessions (Aschenberger et al 2022).…”
Section: Declarations Fundingmentioning
confidence: 99%
“…As the crisis revealed, the non-formal youth work sector was able to continue to support students when school did not manage to reach certain groups (Detyna et al, 2022 ; O’Regan et al, 2022 ). Given this, it appears apposite to include the expertise of the non-formal sector in a more-integrated and sustainable way into a new learning model that is embedded in schools but retains open links with alternative learning environments adding to the literature in this field (Keser Aschenberger et al, 2022 …”
Section: Introductionmentioning
confidence: 99%
“…“Lewin’s formula, B = f (P, E), stressed the need to consider behaviour as a function of both the person and the environment” (Fraser, 2018 , p. 2). More contemporary research provides a holistic conceptualising of learning environments (Keser Aschenberger et al, 2022 ; Manninen et al, 2007 ; Mogas et al, 2021 ; Valtonen et al, 2021 ) infusing physical, technological and informal learning spaces. In this paper, we identify the rationale or need for the re-design of learning environments, drawing on the literature in relation to educational inequality and the potential of youth work approaches informed by a global competencies model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation